Interações entre a cobertura vegetal e os atributos do solo em citros cultivado nos sistemas convencional, orgânico e agroflorestal - Pilon, Lucas Contarato (2017)
Several ways of managing orchards have been used in citros farming, some of that provide efficiency, sustainability and quality in production and the environment. To support these changes and advances to provide a systemic understanding of agroecosystems, the present work was developed. In the first chapter the effort was directed at understanding soil physical, chemical and biological properties as well as the herbaceous cover. In the second chapter techniques that integrate the agroecosystem in a systemic way were used in two distinct parts according principle and use: the first part referring to the Pfeiffer's circular chromatography and in the second part mathematical approach multivariate analysis graph theory. The work was carried out in the municipality of Montenegro, Vale do Caí Region/RS, in five conditions: citros in a conventional system, organic system (biodynamic), agroforestry system (also biodynamic) and two forest areas. The agroecosystems were evaluated at three layers (0-0.05, 0.05-0.20 and 0.20-0.40 m) over four times. Pfeiffer's circular chromatography was used to determine expressive patterns as form and color of chromatograms, as well as their relation with reference standards. The experimental results show that the systems of use and management presented different behavior for most of the properties studied. Different systems such as organic and agroforestry management were distinct from the conventional management with better results pH, phosphorus, CEC and total organic carbon, bulky density and soil porous system, herbaceous cover health and abundance. In the agroforestry system, in turn was better than others in the pH, microporosity and behavior of the fauna of the soil, results as more stable state system. The use of Pfeiffer chromatography allowed to characterize and propose a different understanding of the agroecosystems before the classic methods of soil analysis. Computacional parameters were tested in order to computerize the technique, however visual parameters of analysis continue to be more efficient. Agroecosystems analysis with the multivariate technique provided a better understanding of the systems, allowing us to observe the similarity between the systems studied based on the selected variables. The graph theory was discussed based on the structural frame of the variables within an agroecosystem, in order to integrate soil variables and coverage and with promising possibilities that allow advances in a sustainable agriculture.